Застосування нейронних мереж для прогнозування вологості ізоляції силових маслонаповнених трансформаторів - Василевський, Володимир Валентинович; Каплієнко, Олександр Олегович; Шило, Сергій Іванович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Пропонується застосування нейронної мережі на основі нелінійної авторегресійної моделі з екзогенними входами для прогнозування вологості трансформаторного масла силових маслонаповнених трансформаторів. Із застосуванням інструменту Neural Network Toolbox в середовищі Matlab побудована нейронна мережа, виконано її навчання та тестування. Наведені результати використання побудованої нейронної мережі для прогнозування динаміки вологості трансформаторного масла протягом десяти днів експлуатації. Розглянута можливість використання результатів прогнозування для розрахунку вологості целюлозної ізоляції силового трансформатора.

Purpose. A promising trend is to use neural networks to predict changes in transformer parameters, such as load, temperature of the hottest point, moisture content in cellulose insulation, parameters of transformer oil, etc. The purpose of the article is to develop a model ofthe relationship of the transformers oil temperature with the degree of itsmoisture content using a neural network apparatus. Methodology. We have applied, tested and trained a neural network based on nonlinear autoregressive exogenous model. Results.Using the Neural Network tool, a neural network was built in the Matlab environment. Training and testing of this network was performed using transformer oil parameters, that changes over four months of operation. Results of forecasting of change transformers oil humidity during 10 days of operation are given. The results of the forecast are compared with the actual values of moisture content in transformers oil. The maximum forecast error is 12 percent. Originality.For the first time, we have established the possibility of using neural network based on a nonlinear autoregressive model with exogenous inputs to predict the humidity of transformer oil using the temperature data of the upper and lower layers of the transformer oil. Practical value.The built neural network allows to perform humidity prediction of transformer oil based on the temperature of its upper and lower layers. The results of the forecast can be applied to calculate the moisture content of the cellulose insulation of a power oil-filled transformer.
Application of neural networks to predict the moisture content in oil-filled power transformers insulation
Keywords: целюлозна ізоляція; навчання мережі; cellulose insulation; network training